Peran Tenaga Kesehatan Dalam Penanganan Manajemen Bencana ( Disaster Management) - Mizam Ari Kurniyanti (Jurnal Ilmiah Kesehatan Media Husada, 2012)
Disaster is insident incredible that causes big loss for human and where does that thing can present outdoor human ability to can restrain it. Insides management disaster found several aspects that is aspect mitigation disaster (prevention), emergency moment the happening of disaster, and rehabilitation aspect. Management disaster when does the target disaster rescuing so that risk eliminated. Hodgetts&jones (2002), say that factor that support success in management disaster. One of the successful condition in management disaster is health care. Lack or weakness of health care cause a destruction, loss, and disaster. But exactly this matter is usually is disaster handling weak points in indonesia, belong handling case quakes and tsunami at NAD especially in moment beginning disaster insident, where for the role of health careis very need.